Application of DMAIC Method to Improve the Quality of UMKM Products Roti Kukus Srikaya Balila - Marpaung, Yosefine Rejeki; Ardini, Ni Ketut Shantika; Pribadi, Herodion (Lentera: Multidisciplinary Studies, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a vital role in economic growth, but often struggle with inconsistencies in product quality. This study focuses on Roti Kukus Srikaya Balila, a Denpasar-based UMKM producing steamed bread. It aims to enhance product quality by applying the DMAIC (Define, Measure, Analyze, Improve, Control) methodology within the Six Sigma framework. Key factors were critical to maintaining quality, including taste, texture, appearance, and shelf life. Defect ratios were measured, revealing undercooked bread and inconsistent taste. Solutions were implemented to address these problems, including machinery maintenance, workforce training, and process standardization. The DMAIC methodology proved effective in improving quality consistency, stabilizing processes, and enhancing the competitiveness of UMKM.